2004
DOI: 10.1111/j.1875-595x.2004.tb00299.x
|View full text |Cite
|
Sign up to set email alerts
|

Caries prevalence and its relation to water fluoride levels among schoolchildren in Central Province of Saudi Arabia

Abstract: The caries experience among the primary and intermediate schoolchildren in Riyadh and Qaseem was very high, and that there was no linear correlation between water fluoride level and caries experience in these children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
52
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 15 publications
6
52
6
Order By: Relevance
“…Saudi children have a high caries prevalence and high sweet intake. [9][10][11]13,25 In combination with many newly erupted teeth and a lack of proper oral hygiene, this constitutes a major caries risk. These children need proper information, especially as orthodontic treatment is becoming a common procedure in KSA and is gaining in popularity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Saudi children have a high caries prevalence and high sweet intake. [9][10][11]13,25 In combination with many newly erupted teeth and a lack of proper oral hygiene, this constitutes a major caries risk. These children need proper information, especially as orthodontic treatment is becoming a common procedure in KSA and is gaining in popularity.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] The caries prevalence in teenagers and adolescents in the Kingdom of Saudi Arabia (KSA) is high. 9 This also applies to preschool children. 10 In 300 military school children (6-7 years old) examined for caries, 288 (96%) of the children were diagnosed with decay, while only 4% were clinically caries free.…”
Section: Introductionmentioning
confidence: 99%
“…There have been several surveys conducted locally to determine the nature and magnitude of oral health problems in the provinces. The current literature shows that a majority of oral health surveys have been done on child populations (16)(17)(18)(19)(20). These individual investigations are based on normative assessments and hence may not address oral health status completely at the national level.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that extremely poor dietary habits combined with an apparent lack of awareness, water down the probable effects of Fluoride [26]. Another explanation that has been preferred is that the absence of accurate data on the source of potable water, and an in adequate data on the number of children consuming bottled water makes it difficult to evaluate the relationship between fluoride and dental caries [25]. However, a more recent study, based on the relationship between dental fluorosis and dental caries showed that at levels above 0.6ppm, there was evidence of mild dental fluorosis in a significant number of children [24].…”
Section: Geographic Considerations To Fluoride Exposurementioning
confidence: 99%
“…There have been attempts made to estimate the fluoride levels in the water from different parts of the Kingdom of Saudi Arabia [24].Al Dossary et al, in their extensive study of the relationship between fluoride levels and dental caries in the Kingdom found that children from areas with high levels of fluoride in the water did not show significantly lower caries rates than their counterparts in areas with low levels of fluoride [16,24,25].…”
Section: Geographic Considerations To Fluoride Exposurementioning
confidence: 99%